The Chronic antiplatelet therapy in prevetion of cardiovascular diseases (in population of elderly) from the perspective of oral health: Cardiologic safety versus complications risk. Influence of oral diseases on global health risk in elderly - Marta Wychota; Jan Bieniasz; Konrad Dendys; Marcel Kazzi; Michał Puła (Kazimierz Wielki University, 2023)
Introduction and purpose: Oral cavity diseases are a common problem in everyday clinical practice, particularly important in the context of elderly people affected by numerous chronic diseases, on the verge of frailty. These patients are often characterized by an increased risk of cardiovascular events, but also an increased risk of bleeding, which is the reason for dentists' doubts regarding the maintenance or suspension of chronic antiplatelet therapy in the periprocedural period. The aim of our work is to present the risks of untreated oral diseases and to summarize the current knowledge and recommendations on the use of antiplatelet drugs during surgical dental treatment. Description of the state of knowledge: It has been proven that the ongoing disease processes in the oral cavity exacerbate the course of chronic diseases by several different mechanisms, the best known of which are: opening the gates to the bloodstream, blood circulation of inflammatory mediators and direct colonization of the respiratory tract by microorganisms from the focal point in the oral cavity. According to current research, standard dental surgeries can be safely performed in patients taking antiplatelet drug(s) chronically without the need to discontinue therapy in the periprocedural period. The risk of prolonged or excessive bleeding in such patients is not significantly increased, and bleeding complications that occur can be managed with local haemostasis measures.  Conclusions: Prevention and early treatment of oral diseases can protect against their negative global impact on health. There is no indication to interrupt chronic antiplatelet therapy with one or two drugs prior to standard dental procedures.